White-water rafting guides, leisure behaviour and liminality - Sandro Carnicelli Filho (Tourism & Management Studies)
Tourism, leisure studies, sociology and psychology are some of the academic fields that in recent years have included research related to adventure activities. However, there is still a lack of studies about adventure guides: their personalities, responsibilities and lifestyle. This study aimed to understand the leisure behaviour of white-water rafting guides and the concept of liminality. Exploratory research with whitewater rafting guides in Queenstown, New Zealand, was conducted using as methods of data collection twenty-two in-depth interviews and fifty days of participant-observation. Findings show that the relationship between rafting guides goes beyond the workplace, permeating their social and leisure environment thereby creating liminal states and a ‘liminal-style’. Data also revealed that the relationship between guides and clients is not limited to the rafting environment and sexual encounters between these two groups are recurrent. Finally, the excessive alcohol consumption observed during white-water rafting guides’ leisure activities stimulating a discussion about deviant behaviour as well as the different moral and ethical codes present in their non-ordinary lifestyle.